Mazelas sociais nos Archivos Brasileiros de Hygiene Mental: os discursos sobre alcoolismo, sífilis e imigração (1925-1947) - Mello, Mateus Tatsch de (2020)
The Liga Brasileira de Higiene Mental (LBHM), founded in 1923, collaborated for the consolidation of psychiatry in Brazil through its way of working with governments, by the reflexive action disseminated from its journal, by its community insertion and investment in analysis in various fields of society that have gone beyond the limits of medicine (society, culture, education, politics, health, etc.). The Liga sought to act in the prevention of nervous diseases, protection and protection for the mentally ill and the implementation of a program of mental hygiene and eugenics with a focus on the prophylaxis of factors considered dysgenic. In an attempt to implement these proposals, he made use of the written press, radio stations and lectures in schools and companies, as well as worked with the Government in order to adapt the laws in force in Brazil. In 1925, he started publishing his own journal, the Arquivos Brasileiros de Higiene Mental, which is our primary and main source. In the analysis of all publications published from 1925 to 1947, we list three categories for submitting discourse analysis: alcoholism, syphilis and immigration. This choice was based on the fact that alcoholism would be a degenerative factor that cannot be transmitted from a contagious point of view. Syphilis was chosen because it is exclusively contagious, even with vertical transmission and which, in its most advanced form, caused symptoms in the central nervous system. The third and last category chosen was immigration, due to the fact that it is not an addiction or a disease, but a social factor as considered by many authors. For each text, we highlight a fragment that contained the basis of the proposal of the whole, and we applied the formula, adapted from the methodologies presented by Eni Orlandi and Michel Foucault, to proceed with the discourse analysis: Who speaks? What? In what way? From which location? For whom (interlocution)? When?. With that, we unveiled the discourse behind the text and demonstrated how the Liga managed to establish and operate in Brazil for several decades collaborating in the consolidation of Brazilian psychiatry and expanding its scope of action beyond the healing spaces.